2022
DOI: 10.33200/ijcer.599138
|View full text |Cite
|
Sign up to set email alerts
|

What’s up with WhatsApp? A Critical Analysis of Mobile Instant Messaging Research in Language Learning

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 57 publications
5
31
0
Order By: Relevance
“…The use of technology to mediate communication between language learners was shown to reduce anxiety toward using the language [162]. The game element anonymity, which allows a user to mask their identity or assume the identity of an avatar, fulfils this purpose.…”
Section: Anonymity and Anxietymentioning
confidence: 99%
“…The use of technology to mediate communication between language learners was shown to reduce anxiety toward using the language [162]. The game element anonymity, which allows a user to mask their identity or assume the identity of an avatar, fulfils this purpose.…”
Section: Anonymity and Anxietymentioning
confidence: 99%
“…This contradiction can also be seen in the literature. In some studies, it has been stated that smartphones have a great potential in terms of teaching-learning and by creating a learner-centered teaching process support students' learning and motivation when used appropriately in the classroom (Kartal, 2019;Roblyer, 2016). On the other hand, Shrivastaya and Shrivastaya, (2014) found that students had negative perceptions about using smartphones in the classroom.…”
Section: Smartphone Usage In Classmentioning
confidence: 99%
“…There have been many studies in Mobile Instant Messaging (MIM) and Cloud-based Apps in terms of Elearning. Moreover, most studies focused on the role and the effectiveness of MIM especially WhatsApp in specific fields such as ELT for EFL (Arifani, 2019;Jafari & Chalak, 2016;Kartal, 2019;Minalla, 2018;Ta'amneh, 2017) and Computer Science due to the leaner's familiarity in the English Language. According to Jafari and Chalak (2016), WhatsApp has a positive effect on English vocabulary learning among Iranian EFL learners in comparison to traditional learning, and (Suadi, 2021) stated that WhatsApp has a positive effect on ELT for EFL learning skills.…”
Section: Cloud-based Instant Messaging Appsmentioning
confidence: 99%